Effect of salt nature on structure and ionic conductivity of sodium-doped siloxane-PPO ormolytes - Chaker, J. A.; Dahmouche, K.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Briois, V; Judeinstein, P.; Craievich, A. F. (Elsevier B.V., 2005)
Siloxane-polyoxypropylene (PPO) hybrids obtained by the sol-gel process and containing short polymer chain have been doped with different sodium salts NaX (X = ClO4, BF4 or I). The effect of the counter-ion (X) on the chemical environment of the sodium ions and on the ionic conductivity of these hybrids was investigated by Na-23 NMR, small angle X-ray scattering (SAXS), complex impedance, Raman spectroscopy and differential scanning calorimetry (DSC). Results reveal that the different sodium salts have essentially the same effect on the nanoscopic structure of the hybrids. The formation of immobile Na+ cations involved in NaCl-like species could be minimized by using a low amount of HCl as hydrolytic catalyst. The differences in the ionic conductivity of hybrids doped with different sodium salts were correlated with the proportion of Na ions solvated by ether-type oxygen of the polymeric chains and by the carboxyl oxygen located in the urea groups of the PPO chain extremities. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: hybrid materials; nanocomposites; ionic conductivity; sol-gel processes